2006
DOI: 10.2139/ssrn.956084
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Properties for a Class of Partially Identified Models

Abstract: We propose inference procedures for partially identified population features for which the population identification region can be written as a transformation of the Aumann expectation of a properly defined set valued random variable (SVRV). An SVRV is a mapping that associates a set (rather than a real number) with each element of the sample space. Examples of population features in this class include interval-identified scalar parameters, best linear predictors with interval outcome data, and parameters of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
198
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(202 citation statements)
references
References 66 publications
(58 reference statements)
4
198
0
Order By: Relevance
“…6 Inference is more challenging than estimation as the current literature is inconclusive about the type of con dence interval that should be used in a partial identi cation analysis. There are a number of papers that propose con dence intervals that cover the identi ed set (interval between upper and lower bound) with a xed probability (for example Chernozhukov et al (2007) and Beresteanu and Molinari (2008)). Imbens and Manski (2004) propose a con dence interval which does not cover the identi ed set with xed probability but rather the parameter of interest is covered with xed probability.…”
Section: Miv-boundsmentioning
confidence: 99%
“…6 Inference is more challenging than estimation as the current literature is inconclusive about the type of con dence interval that should be used in a partial identi cation analysis. There are a number of papers that propose con dence intervals that cover the identi ed set (interval between upper and lower bound) with a xed probability (for example Chernozhukov et al (2007) and Beresteanu and Molinari (2008)). Imbens and Manski (2004) propose a con dence interval which does not cover the identi ed set with xed probability but rather the parameter of interest is covered with xed probability.…”
Section: Miv-boundsmentioning
confidence: 99%
“…Both of them are mainly focused on statistical inference. One is given by the work of Beresteanu andMolinari (2006, 2008). They study a class of partially identified models in which the sharp identification region of the parameter vector of interest can be written as a transformation of the Aumann expectation of a properly defined random set.…”
Section: Overviewmentioning
confidence: 99%
“…They then define the notion of "core determining" classes of sets, to find a manageable class of sets for which to check that the dominance condition is satisfied. 6 In order to establish sharpness of the identification region of the parameters of a best linear predictor with interval outcome data, Beresteanu andMolinari (2006, 2008) use the same result involving the capacity functional of a random set due to Artstein (1983) that we use in this paper.…”
Section: Overviewmentioning
confidence: 99%
“…However, there is one precedent to the use of the Aumann expectation as a key tool to describe fundamental features of partially identi…ed models. This is the work of Molinari (2006, 2008), who were the …rst to illustrate the bene…ts of using elements of random sets theory to conduct identi…cation analysis and statistical inference for incomplete econometric models in the space of sets, in a manner which is the exact analog of how these tasks are commonly performed for point identi…ed models in the space of vectors.…”
Section: Introductionmentioning
confidence: 99%
“…They then de…ne the notion of "core determining"classes of sets, to …nd a manageable class of sets for which to check that the dominance condition is satis…ed. Beresteanu and Molinari (2006) use Artstein's (1983 result to establish sharpness of the identi…cation region of the parameters of a best linear predictor with interval outcome data.…”
Section: Introductionmentioning
confidence: 99%